2.HIGHER ST-SEGMENT ELEVATION IN LEAD III THAN LEAD II IN ACUTE INFERIOR MYOCARDIAL INFARCTION CAN BE A PREDICTOR OF SHORT-TERM MORBIDITY AND MORTALITY (Iraqi Journal of Medical Sciences, 2020)
Background:The incidence of mortality and complications are high in patients with acute inferior wall ST-segment elevation myocardial infarction with right ventricular involvement, which has been reported to be an independent predictor of significant complications and in-hospital mortality. Objective:To investigate the feasibility of using electrocardiographic changes in inferior myocardial infarction represented by ST-segment elevation ratio in lead II and III as a predictor of right ventricular infarction and in-hospital morbidity and mortality.Methods:Ninety-nine patients were studied in this prospective study, their ages ranged from 19-90 years, average 58.12 (±12.7 SD). They were presented to the Coronary Care Unit of Basrah General Hospital with acute inferior ST-segment elevation myocardial infarction. The 12 leads plus right-sided precordial electrocardiograms were done to all patients within 12 hours of the onset of symptoms, and ST-segment elevation was measured. ST-segment elevation in lead III exceeding lead II was defined as a ratio of elevation in lead III: II>1. Patients grouped according to ST-segment elevation III:II ratio into either >1 or ?1. In-hospital morbidity and mortality were studied in both groups.Results:ST-segment elevation ratio > 1was detected in 68 patients (68.7%) with acute inferior myocardial infarction at time of admission. Right ventricular infarction was diagnosed in 33 (33.3%) patients, with the majority (32 patients) have ST-elevation ratio > 1. Thirty-Six patients had at least one of the in-hospital complications with significantly higher incidence (51.4%) in patients with higher ST elevation ratio. The mortality was statistically higher when ST segment elevation level in the lead III > than that in the lead II.Conclusion:In patients with inferior STEMI, ST-segment elevation in the lead III more than lead II can be a potential marker of the presence of right ventricular infarction in association with inferior myocardial infarction. Short-term prognosis is possibly worse in the presence of a higher ratio between lead III and II ST-segment elevation. However, further studies are needed to validate this conclusion.Keywords:Inferior MI, right ventricular infarction, ST-segment changesCitation:Al-Mansouri LA, Al-Obaidi FR, Al-Humrani AH. Higher ST-Segment elevation in lead III than lead II in acute inferior myocardial infarction can be a predictor of short-term morbidity and mortality. Iraqi JMS. 2019; 17(3&4): 168-174. doi: 10.22578/IJMS.17.3&4.2
Keywords: Inferior MI; right ventricular infarction; STsegment changes